A comparative method for scaling SOLAS collision damage distributions based on ship crashworthiness – application to probabilistic damage stability analysis of a passenger ship. (3rd July 2022) - Conti, Fabien; Le Sourne, Hervé; Vassalos, Dracos; Kujala, Pentti; Lindroth, Daniel; Kim, Sang Jin; Hirdaris, Spyros
ABSTRACT : SOLAS2020 damage stability regulations are based on probabilistic damage distributions. Those originate from the pooled analysis of collision accidents across a fleet with bias towards cargo ships. This paper introduces a method that accounts for collision-based crashworthiness on ship damage distributions. The method reshapes statistical SOLAS damage distributions for a given ship or structural details for a reference ship section and her reinforced version. Damage reductions may differ depending on ship characteristics and operational scenarios. To mitigate this, a high number of collision scenarios was simulated using the super-element method. It is shown that risk control in terms of damage reduction over the whole range of damages is possible by adding a double hull or by deck reinforcement. Damage reduction is quantified by damage stability analysis of a cruise vessel. It is concluded that installing a double hull on ship vulnerable zones leads to increased A-index.